EVALUATING THE QUALITY OF RESPONSES GENERATED BY CHATGPT - Mandic, Danimir P.; Miscevic , Gordana M.; Bujisic, Ljiljana G. (Metodička teorija i praksa, 2024)
Traditional educational models are becoming outdated; we are facing the challenge of using artificial intelligence, which involves adapting teaching methods, embracing new emerging tools, and utilizing new technologies. In prior research, it has been established that new technologies can lead to benefits related to personalization of education, teaching quality enhancement, monitoring of the learning progress, learning tools development, and increasing motivation. The introduction of ChatGPT, an OpenAI company, has attracted the attention of a diverse population since its inception. We believe that a modern primary school teacher must stay updated with innovations and adapt teaching to new generations of pupils. Therefore, we have conducted research to evaluate the quality of responses in the field of education generated by this application supported by artificial intelligence. Based on the knowledge gained from relevant literature, we have developed a questionnaire that was answered by final-year students of the Faculty of Education - University of Belgrade (Serbia). Firstly, we were interested in determining previous experiences future teachers had with using ChatGPT; subsequently, we assessed to what extent the use of ChatGPT contributed to their work. We have provided opportunities for them to critically evaluate the quality of responses to the questions asked through this application, and finally to express their views on the quality of the responses generated by ChatGPT. The obtained results are presented and discussed. Although most of our interviewees have heard about this application, the experiences they had were not planned for their professional development, making this an area for improving the program of their institutional education. The students expressed their motivation and willingness to evaluate the possibilities of using this language model and learn how to use it, with the awareness that artificial intelligence cannot replace their role, but that it has become a key tool in education, which opens new opportunities for improving the teaching and learning process.